Comprehensive characterization on Ga (In)-bearing dust generated from semiconductor industry for effective recovery of critical metals. (15th April 2019) - Fang, Sheng; Tao, Tianyi; Cao, Hongbin; He, Mingming; Zeng, Xianlai; Ning, Pengge; Zhao, He; Wu, Mingtao; Zhang, Yi; Sun, Zhi
Graphical abstract: Highlights: The natures of MOCVD dust have been obtained by comprehensive characterizations. The distributions of GaN and metallic indium phase are crucial to metal recycling. Some treatment strategies for MOCVD dust are preliminarily evaluated and discussed. 89.59% of gallium is selectively leached using NaOH. Abstract: Gallium (indium)-bearing dust generated from semiconductor industry is an important secondary resource for critical metal recycling. However, the diverse and distinct physicochemical natures of such waste material have made its recycling less effective, e.g. low extraction rate and complex treatment procedures. This research is devoted to gaining in-depth knowledge of the physical and chemical properties of such waste, including the chemical composition, physical phases, particle size distribution and chemical-thermal properties with a series of technologies. As a consequence, the occurrence and distribution of GaN and metallic indium phases are found to be crucial to efficient metal recycling. The thermal-chemical behavior shows that continuous oxidation occurred in the air atmosphere, indicating that heat-treatment followed by acid leaching is feasible to improve their recycling efficiencies. This process is able to leach 80.35% of gallium and 95.78% of indium with one-step operation. Furthermore, different treatment strategies for the waste material are preliminarily evaluated and discussed for the aim of metal recovery. The results show that gallium can be selectively recycled with recycling rate of 89.59% using alkaline leaching. With this research, the understanding on the recyclability of different metals and possibilities of selective recovery can be improved. It provides guidelines during the stage of decision-making for critical metal recycling in order to achieve efficient resource circulation.